Representasi Visual Pilihan Gaya Hidup dalam Konten Digital Pemerintah: Analisis Semiotika Multimodal Poster Instagram @kemenpora - Agnes Ariyanti Normasari; Atika, Hani (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aims to analyze the representation of healthy lifestyle ideology in government digital campaigns through the Instagram content of the Ministry of Youth and Sports of the Republic of Indonesia (@kemenpora). The rapid development of social media as a medium for public communication has encouraged government institutions to utilize digital platforms to deliver policy messages in a more persuasive, visual, and interactive manner. In this context, social media content functions not only as a source of information, but also as a space  for the production of meaning and ideology that shapes public understanding of health and lifestyle. This research employs a qualitative approach using Kress and van Leeuwen’s multimodal semiotic analysis, which includes three metafunctions of meaning: representational, interactive, and compositional. The analysis is further enriched by Roland Barthes’ semiotic framework at the levels of denotation, connotation, and myth to uncover the deeper ideological meanings embedded within the campaign visuals. The findings reveal that @kemenpora’s visual content constructs a dichotomy between unhealthy food consumption and physical activity as opposing lifestyle choices. At the mythological level, the campaign reproduces the ideology of healthism, which positions health as solely an individual responsibility while obscuring the social and structural dimensions influencing public health conditions. This study concludes that government digital campaigns function not only as instruments of public education, but also as strategic communication tools that construct healthy lifestyle ideology within the digital sphere.